A new species of Sextonia Chevreux, 1920 (Crustacea: Amphipoda: Liljeborgiidae) from the Okhotsk Sea - Labay, Vjacheslav S. (Zootaxa, 2017)
A new amphipod species, Sextonia caecus sp. nov., from the shelf of northern Sakhalin Island (Russian Far East) is described. A key to the amphipod species of the genus Sextonia is given.